System Design and Implementation of Online Admission System at XYZ University - Tuhuteru, Hennie; Reynaldi Siwalette (Pusat Penelitian dan Pengabdian Pada Masyarakat Sekolah Tinggi Manajemen Informatika dan Komputer AKBA Makassar, 2022)
Digital transformation that is developing along with the industrial revolution 4.0 makes all sectors must be able to adapt and compete more competitively. XYZ University in Ambon, Maluku is currently still carrying out the admissions process manually and using the Google Form. This study aims to design and implement a web-based admissions system at XYZ University. Thus, this system can help the admissions committee and the new students who will register from anywhere and at any time. The method used in this research is Agile Software Development (ASD). This method is very popular in the IT industry today because of its speed and ability to adapt to the changing needs of users. ASD has several models and the one used in this study is the Scrum model, where each Product Backlog obtained from the user is divided into several sprints to make software development easier and faster. The results of this study have been tested and are running well from an operational and functional standpoint to help the admissions committee and new students in the registration process. The conclusions based on the results of this study are (1) the ASD method can help and speed up the software development process, and can be adapted to user needs because it is end-user-centered; (2) This system can help solve research problems, in this case the admissions committee at XYZ University to manage online admissions of new students. In addition, this system can make the process of admitting new students easier and more affordable for students to register from anywhere and at any time.